2004
DOI: 10.1023/b:aseb.0000007462.97961.5a
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Sexual Dysfunction and Substance Use Among a Community Epidemiological Sample

Abstract: This study examines the prevalence of DSM-III sexual dysfunctions and their association with comorbid drug and alcohol use in a community epidemiologic sample. The data for these analyses are based on the Epidemiological Catchment Area Project, a multistage probability study of the incidence and prevalence of psychiatric disorders in the general population conducted in 1981-83. Only the sample of 3,004 adult community residents in the St. Louis area was queried on DSM-III sexual dysfunctions of inhibited orgas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
105
0
12

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(134 citation statements)
references
References 31 publications
17
105
0
12
Order By: Relevance
“…These gave some support to other studies reporting similar associations. 20,21 The current study further found that Chinese women with late menarche (13-14 vs p12 years) were at high risk of having SD (multivariate analysis), which is supported by another study. 22 Associations were found between SD and RTI, cervical erosion, menstrual disorders and use of IUD, which have not been well documented in the literature.…”
Section: Discussionsupporting
confidence: 85%
“…These gave some support to other studies reporting similar associations. 20,21 The current study further found that Chinese women with late menarche (13-14 vs p12 years) were at high risk of having SD (multivariate analysis), which is supported by another study. 22 Associations were found between SD and RTI, cervical erosion, menstrual disorders and use of IUD, which have not been well documented in the literature.…”
Section: Discussionsupporting
confidence: 85%
“…A somewhat higher prevalence of orgasmic dysfunction (30%) was reported from Finland. 2 In other studies, 16,18,19,26,27,32 the prevalence of orgasmic dysfunction was much lower (11%e16%), whereas that of mild orgasmic dysfunction was remarkably high (approximately 60%) in two Nordic countries, where identical methodology was used. Thus, in these two countries, more than 80% of all sexually active women 18 to 74 years old reported some degree of orgasmic dysfunction.…”
Section: Orgasmmentioning
confidence: 89%
“…The prevalence of dyspareunia was reported as low as 1% in Australian women 34 and 2% in elderly British women, 35 whereas other studies found that dyspareunia was present in as many as 14% to 27% of women. 16,18,19,26,27,32 Several investigations described increasing dyspareunia with increasing age. 17,36 The Global Study of Sexual Attitudes and Behavior 20 reported pain during sexual intercourse to range from 5% in Northern Europe to 22% in Southeast Asia.…”
Section: Dyspareunia and Vaginismusmentioning
confidence: 99%
“…Por un lado, se ha observado que, a dosis bajas y a corto plazo, el alcohol (Emanuele y Emanuele, 1998), las benzodiacepinas (Smith, 2007), el cannabis (Lévy y Garnier, 2006;McKay, 2005), la cocaí-na (Buffum, Moser y Smith, 1988;Peugh y Belenko, 2001;Rosen, 1991), los opioides (Hyatt y Bensky, 1999), las anfetaminas y las metanfetaminas (Degenhardt y Topp, 2003;Kurtz, 2005), y los alucinógenos (Lévy y Garnier, 2006) pueden llegar a mejorar diversas áreas del funcionamiento sexual, aunque habitualmente estos efectos son efímeros ya que se produce una rápida habituación. A dosis más elevadas y/o en periodos de tiempo más prolongados, los efectos de las drogas son devastadores, afectando tanto a los aspectos físiológicos del ciclo sexual (Argiolas, 1999;Crenshaw y Goldberg, 1996;Cocores, Miller, Pottash y Gold, 1988;Johnson, Phelps y Cottler, 2004), como a los aspectos psicológi-cos de la sexualidad (Aguilar et al, 2008;Ávila Escribano, Pérez Madruga, Ólazabal Ulacia y López Fidalgo, 2004;La Pera et al, 2003;Lévy y Garnier, 2006;Peugh y Belenko, 2001;Rosen, 1991;Smith, 2007). Asimismo, es importante destacar la influencia que el tabaco tiene sobre la respuesta sexual humana, tanto a corto, como a largo plazo (Gades et al, 2005;Shiri et al, 2004).…”
Section: Introductionunclassified